Atrial remodelling and dysfunction in hypertrophic cardiomyopathy: prognostic role and therapeutic target - Chiara Piazzai; Alessio Petrone; Andrea Stefanini; Flavio D’Ascenzi; Iacopo Olivotto; Iacopo Olivotto; Matteo Cameli (Frontiers in Cardiovascular Medicine)
IntroductionHypertrophic cardiomyopathy (HCM) is a common genetic cardiac disease marked by abnormal ventricular hypertrophy. Recent studies have highlighted that left atrial (LA) remodelling—including dilation, fibrosis, and functional impairment—plays a key role in disease progression and prognosis, notably increasing the risk of atrial fibrillation (AF) and stroke.Material and methodsThis review article systematically examines published clinical, imaging, and interventional studies. The analysis focuses on identifying the determinants of atrial myopathy, its relationship with diastolic dysfunction and left ventricular outflow tract obstruction (LVOTO), and the effects of therapeutic interventions such as septal reduction therapy and cardiac myosin inhibitors.ResultsThe findings reveal that LA remodelling in HCM is characterized by increased LA volume, reduced atrial strain, and prolonged conduction times—all of which are strongly linked to the onset and recurrence of AF. Moreover, interventions that reduce LVOTO (e.g., surgical myectomy) have been shown to induce LA reverse remodelling and improve diastolic parameters. Emerging therapies, like cardiac myosin inhibitors, also improve LV function but present complex effects on atrial performance, with some evidence suggesting a reduction in atrial strain that warrants further investigation.ConclusionAtrial remodelling is a significant marker of disease severity in HCM and an important independent predictor of adverse outcomes, including AF and cardioembolic events. Early detection through comprehensive multimodal imaging and timely therapeutic intervention can potentially mitigate these risks, making atrial myopathy both a critical prognostic factor and a promising therapeutic target.